Position for Site-Specific Attachment of a DOTA Chelator to Synthetic Affibody Molecules Has a Different Influence on the Targeting Properties of Ga-Compared to In-Labeled Conjugates - Hadis Honarvar; Joanna Strand; Anna Perols; Anna Orlova; Ram Kumar Selvaraju; Amelie Eriksson Karlström; Vladimir Tolmachev (Molecular Imaging)
Affibody molecules, small (7 kDa) scaffold proteins, are a promising class of probes for radionuclide molecular imaging. Radiolabeling of Affibody molecules with the positron-emitting nuclide 68 Ga would permit the use of positron emission tomography (PET), providing better resolution, sensitivity, and quantification accuracy than single-photon emission computed tomography (SPECT). The synthetic anti-HER2 Z HER2:S1 Affibody molecule was conjugated with DOTA at the N-terminus, in the middle of helix 3, or at the C-terminus. The biodistribution of 68 Ga- and 111 In-labeled Affibody molecules was directly compared in NMRI nu/nu mice bearing SKOV3 xenografts. The position of the chelator strongly influenced the biodistribution of the tracers, and the influence was more pronounced for 68 Ga-labeled Affibody molecules than for the 111 In-labeled counterparts. The best 68 Ga-labeled variant was 68 Ga-[DOTA-A1]-Z HER2:S1 which provided a tumor uptake of 13 ± 1 %ID/g and a tumor to blood ratio of 39 ± 12 at 2 hours after injection. 111 In-[DOTA-A 1 ]-Z HER2:S1 and 111 In-[DOTA-K 58 ]-Z HER2:S1 were equally good at this time point, providing a tumor uptake of 15 to 16 %ID/g and a tumor to blood ratio in the range of 60 to 80. In conclusion, the selection of the best position for a chelator in Affibody molecules can be used for optimization of their imaging properties. This may be important for the development of Affibody-based and other protein-based imaging probes.